2014
DOI: 10.1056/nejmoa1304617
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Infections with Avian Influenza A(H7N9) Virus in China

Abstract: Most persons with confirmed H7N9 virus infection had severe lower respiratory tract illness, were epidemiologically unrelated, and had a history of recent exposure to poultry. However, limited, nonsustained human-to-human H7N9 virus transmission could not be ruled out in four families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
618
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 623 publications
(648 citation statements)
references
References 53 publications
21
618
1
8
Order By: Relevance
“…The large majority of persons identified with influenza A(H7N9) virus infection presented with severe disease8 and approximately 40% died2. Persons with mild, atypical, and asymptomatic infections are far less likely to be tested for influenza A(H7N9) and will usually not seek health care.…”
Section: Introductionmentioning
confidence: 99%
“…The large majority of persons identified with influenza A(H7N9) virus infection presented with severe disease8 and approximately 40% died2. Persons with mild, atypical, and asymptomatic infections are far less likely to be tested for influenza A(H7N9) and will usually not seek health care.…”
Section: Introductionmentioning
confidence: 99%
“…There have been four influenza pandemics within the past 100 y, including the devastating H1N1 outbreak in 1918 (6) and the H1N1 outbreak in 2009 (7). Although zoonotic avian viruses of the H5N1, H7N3, H7N7, H7N9, H9N2, and H10N8 subtypes have failed to spread in humans, fatality rates have approached 60% for some of these outbreaks (8,9). Mutations that can facilitate human transmission of these zoonotic viruses are being identified (10,11).…”
mentioning
confidence: 99%
“…9 An epidemiological study in China between May 2013 and May 2014 showed 6.7% of case contacts developed H7N9 antibodies, suggesting that human-to-human transmission occurs and could cause mild or asymptomatic infection. 10 Both human-to-human household and hospital clusters have been described. 11,12 Transmissibility of avian influenza to humans depends on a balance of activities of the viral surface glycoproteins HA and neuraminidase (NA).…”
Section: Concern For An Avian H7n9 Influenza Pandemicmentioning
confidence: 99%